2013
DOI: 10.2105/ajph.2012.300948
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Examination of the Influence of State Tobacco Control Programs and Policies on Youth Smoking

Abstract: Objectives. We examined the influence of tobacco control policies (tobacco control program expenditures, smoke-free air laws, youth access law compliance, and cigarette prices) on youth smoking outcomes (smoking susceptibility, past-year initiation, current smoking, and established smoking). Methods. We combined data from the 2002 to 2008 National Surveys on Drug Use and Health with state and municipality population data from the US Census Bureau to assess the associations between state tobacco control policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 17 publications
3
64
1
Order By: Relevance
“…[2][3][4] Contrary to previous work, however, we found no significant association between state tobacco control funding and youth smoking rates. [2][3][4] At the same time, previous studies that have found evidence for effects of state funding on youth smoking have not accounted for media campaign exposure in the same model. Since media campaigns most likely represent the largest expenditure in state tobacco control programmes, 24 we suspect that this finding can be explained by the fact that we measured and accounted for the effects of antismoking ad exposure in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Contrary to previous work, however, we found no significant association between state tobacco control funding and youth smoking rates. [2][3][4] At the same time, previous studies that have found evidence for effects of state funding on youth smoking have not accounted for media campaign exposure in the same model. Since media campaigns most likely represent the largest expenditure in state tobacco control programmes, 24 we suspect that this finding can be explained by the fact that we measured and accounted for the effects of antismoking ad exposure in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…1 There is strong evidence that comprehensive tobacco control programmes were a major contributor to the observed declines in youth smoking prevalence during this time period. [2][3][4] Mass media campaigns are widely accepted as an integral part of these programmes, 4 5 and numerous studies link campaign exposure to reduced smoking prevalence in the USA. [5][6][7][8] A parallel body of work has sought to identify characteristics of effective antismoking advertisements (ads; public service announcements (PSAs)), emphasising the importance of both thematic content and stylistic features.…”
Section: Introductionmentioning
confidence: 99%
“…6 A wide array of research has suggested that excise taxes and clean air policies are efficacious tobacco control policy tools, but these studies have come with several limitations that prohibit linking policy with actual individual-level behavior. For clean air policies, studies have inferred the effects of such prohibitions through cohort effects, 7 relied on cross-sectional data, 810 have not considered city-level policy, 913 or used data within a single locality. 1415 Studies have also found robust effects of excise taxes on tobacco use.…”
mentioning
confidence: 99%
“…For example, during the 1990s California's comprehensive tobacco control programme, which started in 1989, increased the population cessation rate significantly when compared to other US states with weak tobacco control programmes [14]. In addition, evidence from the United States showed that comprehensive state tobacco control programmes were effective in decreasing adult smoking prevalence [15] and curbing youth smoking [16]. Apart from the general effect of the 2009 Act, we found little difference by demographic factors.…”
Section: Discussionmentioning
confidence: 55%